Q: What is 7 23 n 9 112?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

n - 7 = 9 n = 16

23*n - 9

7n - 11n = 3n + 9 Collecting all the terms with n on the left, (7-11-3)n = 9 -7n = 9 Divide both sides by -7 to give n = -9/7

7/8 = 14/nMultiply each side of the equation by 8 :7 = 112/nMultiply each side by 'n' :7n = 112Divide each side by 7:n = 16

112/8=n 14=n check= 8x14=112

Related questions

To solve this, divide 112 into 784. n = 7

n - 7 = 9 n = 16

23*n - 9

the equation is: (n / 8 ) - 5 = 9 the number is 112. 112 / 8 is 14 5 less than 14 is 9

9 ,16 ,23, 30 We note that there is a difference of '7' between terms. So the first part of the 'nth' term is 7n. Note the '7' becomes multiple. Next we need to find the constant 'c' So taking the first term (n = 1) we write. 7n + c = 9 7(1) + c = 9 7 + c = 9 c = 2 So the 'nth' term is '7n + 2' To verify , try the 3rd term n= 3 then answer should be '23'. 7(3) + 2 = 21 + 2 = 23 As required.

The rule for the nth term is t(0) = 23 t(n) = mod[t(n-1) + 2n-1, 26] for n = 1, 2, 3, ...

36° 3′ 18.94″ N, 112° 7′ 18.61″ W36.055261, -112.121836

7 more than the quotient of a number n and 4 is 9

7n - 11n = 3n + 9 Collecting all the terms with n on the left, (7-11-3)n = 9 -7n = 9 Divide both sides by -7 to give n = -9/7

t(n) = 5 - 7n for n = 1, 2, 3, ... The difference between each term is -7, therefore the nth term will be: t(n) = -2 + -7 × (n - 1) = -2 + 7n + 7 = 5 - 7n

n to the power of 9

7/8 = 14/nMultiply each side of the equation by 8 :7 = 112/nMultiply each side by 'n' :7n = 112Divide each side by 7:n = 16